2019
DOI: 10.3389/fimmu.2019.01459
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Transcriptomic and Genomic Analysis Identifies a Gene Signature Associated With the Response to Anti-TNF Therapy in Rheumatoid Arthritis

Abstract: Background: Rheumatoid arthritis (RA) is the most frequent autoimmune disease involving the joints. Although anti-TNF therapies have proven effective in the management of RA, approximately one third of patients do not show a significant clinical response. The objective of this study was to identify new genetic variation associated with the clinical response to anti-TNF therapy in RA. Methods: We performed a sequential multi-omic analysis integrating different sources of molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 116 publications
(108 reference statements)
0
17
0
Order By: Relevance
“…At the cellular and tissue level, RA is characterized by the chronic infiltration of immune cells in the synovial membrane (9). To understand biologic processes associated with anti-TNF response, several transcriptomic and epigenetic studies have been conducted using the synovium and blood from patients with RA (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Those studies have demonstrated that transcriptomic and epigenetic profiling have the potential to predict response to anti-TNF therapies before treatment.…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular and tissue level, RA is characterized by the chronic infiltration of immune cells in the synovial membrane (9). To understand biologic processes associated with anti-TNF response, several transcriptomic and epigenetic studies have been conducted using the synovium and blood from patients with RA (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Those studies have demonstrated that transcriptomic and epigenetic profiling have the potential to predict response to anti-TNF therapies before treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although a few study have looked at synovial membrane factors as predictors of response to csDMARDs ( Vieira-Sousa, 2011 ) and at the effect of treatment on synovitis ( Haringman, 2005 ), none to our knowledge include the analysis of MCs. In recent years, the attention has switched to biologic treatment, and a number of publications described both histological and molecular signatures that can predict treatment response to biologics ( Dennis et al., 2014 ; Aterido et al., 2019 ). However, to date, the relevance of synovial MCs in relation to response to conventional or biologic DMARDs has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge will facilitate the identification of biomarkers and drug discovery and contribute to the development of precision therapy for RA ( 401 ). Besides, another study performed a sequential multi-omics analysis integrating transcriptomics and genomics to identify gene signatures associated with the response to anti-TNF therapy in RA patients ( 402 ). Using transcriptomic data from the RA synovium, thirteen gene co-expressed modules were found to be associated with anti-TNF response.…”
Section: Multi-omics In Precision Medicine Of Ramentioning
confidence: 99%